A novel fabrication approach for impact resistance laminated ceramics. (15th August 2015) - Li, Liangjun; Cheng, Laifei; Fan, Shangwu; Gao, Xiaoju; Xie, YuPeng; Zhang, Litong
Graphical abstract: The dynamic compressive properties of the laminated ceramics with Zr tape/4 Si3 N4 tapes stacked structure. Highlights: Tape casting and reactive hot pressing allow producing laminated ceramics with controlled interfaces and designed microstructure that display high strength, strain to fracture and good energy absorptivity upon impact. Abstract: A novel approach via tape casting and reactive hot pressing was presented to fabricate impact resistance laminated ceramics, and the designability of soft and hard interbedded microstructure, the controllability of in-situ interfaces and the dynamic performance potentials of the laminated ceramics were investigated. Laminated ZrO–Zr2 CN/Si3 N4 ceramics with designable microstructure and controllable in-situ interfaces were fabricated by synergistically designing the thickness of the matrix and controlling the heating rate. The dynamic compressive responses of the laminated ceramic were tested with a range of high strain rates from 1.1 × 10 3 s −1 to 3.3 × 10 3 s −1, and the results showed that the laminated ceramics obtain excellent dynamic compressive performance with high dynamic strength of 1.1–2.6 GPa, large pseudoplastic strain of 7.7–12.2% and good energy absorptivity of 23.34–34.59%. Multi-reflection and attenuation of stress wave at interfaces were the main reason of excellent comprehensive performance.